2022
DOI: 10.7759/cureus.22136
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Profile and Factors Affecting Outcomes in Elderly Patients Admitted to the Medical Intensive Care Unit of a Tertiary Care Hospital

Abstract: BackgroundIn recent years, there is an increase in the proportion of the elderly population in the world. With an increase in patients' age, there is a change in the comorbidities and causes for Intensive care unit (ICU) admissions. More studies are needed to redefine healthcare delivery to elderly patients admitted to ICU. AimsThe aims are to assess the disease pattern and outcome in elderly patients admitted to the Medical ICU and to determine factors affecting the outcomes in elderly patients admitted to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 15 publications
0
1
1
Order By: Relevance
“…Similar findings were reported in a study conducted by Ball et al, greater mortality rates in patients with prolonged ICU stay may be either because of severe illness or ICU-related complications like ventilator-associated pneumonia, central venous catheterassociated infection, urinary catheter-associated infection, venous thromboembolism and stress ulcers [11,21,25].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Similar findings were reported in a study conducted by Ball et al, greater mortality rates in patients with prolonged ICU stay may be either because of severe illness or ICU-related complications like ventilator-associated pneumonia, central venous catheterassociated infection, urinary catheter-associated infection, venous thromboembolism and stress ulcers [11,21,25].…”
Section: Discussionsupporting
confidence: 88%
“…The mortality rate over two years was 28.8% (n=59); males accounted for 47.5% (n=28), and females accounted for 52.5% (n=31), which was lessened when compared to 36.7% in a study conducted by Upparakadiyala et al and published in 2022 [11]. However, in a study conducted by Thangam & Deepa, the mortality rate was 25%, which could be attributed to admission diagnosis as acute cardiac and COVID-19 infection cases were admitted to dedicated intensive care units.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…This may be due to the tendency of extubating the post-operative elderly patients in the ICU. On evaluating the mortality rate, the mortality rate among elderly in our ICU was 35.2% which was lower than in the study of elderly done by Upparakadiyala et al,11 in Tirupati, India, but higher than Thangam and Deepa 5 in Chennai and Oh et al, 6 in South Korea. This shows that the care of our elderly is comparable to other developing nations.…”
Section: Discussioncontrasting
confidence: 61%
“…The duration of ICU stay in this study was higher than in earlier reported studies. 3 , 4 , 8 , 12 Probably this variation in the length of ICU stay may be due to differences in the severity of disease patterns, infections, and other complications. 12 In this study, the association between APACHE II scores of the patients and the duration of ICU stay was insignificant, as observed in previous studies.…”
Section: Discussionmentioning
confidence: 99%